2018
DOI: 10.1002/ejic.201800853
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress and Challenges of Micro‐/Nanostructured Transition Metal Carbonate Anodes for Lithium Ion Batteries

Abstract: Lithium ion batteries (LIBs) have attracted tremendous interest in electric vehicles and smart grids, due to their inherent advantages of being powerful and environmentally benign. However, their performance is presently far from meeting the continually increasing demands for long-durance mileage and long lifespan. High-performance anodes with high specific capacity and long cyclability are of great significance to high-energy/high-power lithium ion batteries; however, there are still great challenges in advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Although undesirable, this material is expected to show similar chemistry to CuO, with respect to lithiation. We note that previous literature has described the use of transition metal carbonates an anode material . The absence of the GO peak at 2 θ ≈11° in Cu‐3, Cu‐4, and Cu‐5 indicates that the graphene is present as mono/few layers in the graphene hybrid materials.…”
Section: Resultsmentioning
confidence: 99%
“…Although undesirable, this material is expected to show similar chemistry to CuO, with respect to lithiation. We note that previous literature has described the use of transition metal carbonates an anode material . The absence of the GO peak at 2 θ ≈11° in Cu‐3, Cu‐4, and Cu‐5 indicates that the graphene is present as mono/few layers in the graphene hybrid materials.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous reports have shown that CoCO 3 delivers a higher capacity than its theoretical value, as the conversion reaction product, Li 2 CO 3 , participates reversibly in the electrochemical reaction via the redox reaction of C 4+ to low valence C. [ 10,11 ] Owing to the reversible redox reaction of carbon in Li 2 CO 3 , transition metal carbonates exhibit higher practical capacities than transition metal oxides with the same metal oxidation state, despite their lower theoretical capacities. [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, previous reports have shown that CoCO 3 delivers a higher capacity than its theoretical value, as the conversion reaction product, Li 2 CO 3 , participates reversibly in the electrochemical reaction via the redox reaction of C 4+ to low valence C. [10,11] Owing to the reversible redox reaction of carbon in Li 2 CO 3 , transition metal carbonates exhibit higher practical capacities than transition metal oxides with the same metal oxidation state, despite their lower theoretical capacities. [12,13] Similarly, it was also reported that the LiOH formed by the conversion reaction of Co(OH) 2 contributes to extra reversible capacity in the presence of nanosized Co metal. [14] Hu et al demonstrated that some -OH groups at the surface of RuO 2 lead to LiOH formation, which then reacts with lithium to form Li 2 O and LiH phases, thereby providing unexpected additional capacity.…”
mentioning
confidence: 97%
“…These reports assume that not only the crystal structure but also the physical shape (or morphology) of the anode materials, such as Si, hematite (Fe 2 O 3 ), and LMO (Li M O 2 , M = Co, Ni, Mn) can significantly affect the performance of LIBs, implying that control of anode nanostructures is necessary. As one of the strategies, nanoscale pattern formation of lithium carbonate (Li 2 CO 3 ) on the LIB anode such as graphite can provide good passivation and may also promote rich solid electrolyte interphase (SEI) at interface of anode and electrolyte [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%